Analisis Sustainability Literacy (Literasi Keberlanjutan) Peserta Didik Fase E Pada Isu Virus di SMAN 1 Batang Anai : Penelitian - Hamdani, Aisyah; Rahmawati D; Muhyiatul Fadilah; Fitri Olvia Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the level of sustainability literacy of Phase E students on the issue of viruses at SMAN 1 Batang Anai. The method used is descriptive quantitative with a sample of 179 students selected through simple random sampling. The data in this study were obtained through the results of a test instrument in the form of multiple-choice questions (objective) arranged based on aspects of sustainability literacy. These test questions have been tested and proven to meet the validity criteria. The results show that the level of sustainability literacy of students in the knowledge aspect is in the medium category (60.68%), the knowledge-skills aspect (57.43%) is in the low category and the mindset aspect (58.47%) is in the low category. Thus, it can be concluded that the level of sustainability literacy of Phase E students on the issue of viruses at SMAN 1 Batang Anai is still in the low category.